Bilateral homonymous visual field defects as initial manifestation of multiple sclerosis. Issue 3 (March 1991) - Sanchez-Dalmau, B; Goñi, F J; Guarro, M; Roig, C; Duch-Bordas, F
Abstract : Symptomatic suprageniculate lesions in multiple sclerosis expressed as a visual field defect are infrequent. The present case developed a bilateral homonymous defect as the initial and unique symptom of the disease. It was confirmed by nuclear magnetic resonance imaging, which disclosed extensive demyelinating areas in both optic nerve radiations. The mode of onset, perimetric findings, and unusual presentation of this condition are briefly discussed.